2022
DOI: 10.3390/ma15134635
|View full text |Cite
|
Sign up to set email alerts
|

Single Dense Layer of PEO Coating on Aluminum Fabricated by “Chain-like” Discharges

Abstract: Reducing the loose-layer-to-dense-layer ratio in PEO coatings on aluminum and its alloys is the key to improving their corrosion resistance and expanding their applications in the aerospace industry and other fields. In this paper, we describe the discharge evolution during the PEO process in exhaustive detail and report the appearance of a novel “chain-like” discharge for the first time. We investigated the microstructure and composition of PEO coatings using a scanning electron microscope (SEM) equipped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…[56,67] These methods resulted in dense PEO coatings by controlling or reducing the discharges at the interface between the substrate and the coating. [68,69] Although such soft discharges can reduce the porous-layer-to-dense-layer ratio, achieving a single dense layer is difficult. However, Zhu et al used a novel chain-like discharge method for the PEO coating preparation on Al substrates.…”
Section: Inner Layermentioning
confidence: 99%
“…However, Zhu et al used a novel chain‐like discharge method for the PEO coating preparation on Al substrates. [ 69 ] This technique enabled the formation of a single dense layer with 2.8% porosity exhibiting high corrosion protection behaviors, good adhesion, and high hardness.…”
Section: Peo Coating Structurementioning
confidence: 99%
“…The combination of high micro-hardness and wear resistance with corrosion resistance ensures the wide use of products with such coatings in many industries [1][2][3]. A large number of studies has been devoted to improving the MAO process under consideration, among which one can note: imparting new properties to coatings by adding nanoparticles to the electrolyte [4][5][6], searching for new applications of MAO coatings [7,8], improving their characteristics [9][10][11][12], optimization [13][14][15][16][17][18] and control [19,20] of the oxidation process. A number of studies are devoted to the problems of identification of complex technical systems, in particular, in [21] a new algorithm for identification of a linear-time-invariant system using MATLAB is proposed.…”
Section: Introductionmentioning
confidence: 99%